2005
DOI: 10.1016/j.crvi.2005.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature and nutritional requirements for mycelial growth of Eutypa lata, a vineyard pathogenic fungus

Abstract: Eutypa dieback (dying arm disease, eutypiosis) is a very devastating disease in many grape-producing areas around the world. This vascular disease is induced by the ascomycete Eutypa lata Pers. Fr. Tul & C. Tul. invading the trunk by pruning wounds. The environmental factors and the nutritional requirements regulating fungus development are yet poorly known. This work shows that the isolated strain of E. lata was able to grow in a large temperature range (2-30 • C). However, a higher temperature (35 • C) prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…During the fungal attack, the degradation of lignin, cellulose, and hemicellulose leads to the formation of cavities in the walls and thus, makes the wood brittle [ 70 ]. In vitro studies highlighted the strong lysis activity of plant cells (leaves or cell suspension) by fungal filtrate proteins, including hydrolytic enzymes such as chitinases, β-1.3-glucanases, glycosidases, and xylanases [ 71 ]. Some studies also revealed the presence of toxic molecules secreted by the fungus under in vitro conditions, including acetylene and heterocyclic compounds.…”
Section: The Complexity Of Grapevine Trunk Diseasesmentioning
confidence: 99%
“…During the fungal attack, the degradation of lignin, cellulose, and hemicellulose leads to the formation of cavities in the walls and thus, makes the wood brittle [ 70 ]. In vitro studies highlighted the strong lysis activity of plant cells (leaves or cell suspension) by fungal filtrate proteins, including hydrolytic enzymes such as chitinases, β-1.3-glucanases, glycosidases, and xylanases [ 71 ]. Some studies also revealed the presence of toxic molecules secreted by the fungus under in vitro conditions, including acetylene and heterocyclic compounds.…”
Section: The Complexity Of Grapevine Trunk Diseasesmentioning
confidence: 99%
“…Harvesting was at the end of September, corresponding to the end of a cycle for vine: leaves and cordons are mature, and nutrients are stored in the xylem sink to face the winter period. Moreover, from the start of spring, the pathogen is exposed to optimal growth conditions, in particular temperature (Amborabé et al 2005). Samples were taken from the trunks of eight infected vines, in the brown and wedge-shaped area, in discoloured and apparently healthy tissue at the margin of the canker, and from the base and apex of annual canes.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Mycelium was grown on a sterile medium containing yeast nitrogen base (YNB W/O amino acids and ammonium sulphate, Difco 233520, Detroit) at 1.7 g l −1 supplemented with glucose (10 g l −1 ) as carbon source and proline (5 g l −1 ) as nitrogen source (Amborabé et al 2005). Culture was initiated in 250 ml medium by addition of a mycelium disc (1 cm diameter) taken in a culture made on the same medium solidified with agar at 20 g l −1 .…”
Section: Methodsmentioning
confidence: 99%